Investigation of the cytotoxicity induced by didocosahexaenoin, an omega 3 derivative, in human prostate carcinoma cell lines - Robinson, Glenn F.; Sooda, Kartheek KY; Phillips, Roger M.; Allison, Simon J.; Javid, Farideh A. (Current research in pharmacology and drug discovery, 2022)
The aim of the present study was to investigate the cytotoxicity induced by an omega-3 derivative, didocosahexaenoin (Dido) on human prostate carcinoma cells and to compare the cytotoxicity to that of docosahexaenoic acid (DHA). Different carcinoma- and non-carcinoma cells were exposed to various concentrations of omega-3 compounds at varying exposure times and the cytotoxicity was measured by MTT assay. The mechanism of Dido-induced apoptosis was investigated in prostate carcinoma cells. Dido induced stronger cytotoxicity than DHA in human prostate carcinoma cells in a dose- and time-dependent manner. Dido was also more selective and potent in inducing cytotoxicity in prostate carcinoma cells than other carcinoma cell lines tested. Pre-treatment with Dido increased the level of reactive oxygen species (ROS) in prostate carcinoma cells. Pre-treatment with various antioxidants reduced the cytotoxicity induced by Dido. Pre-treatment with Dido ≥30 μM also induced apoptosis which was suggested to involve an externalisation of phosphatidyl serine, a significant increase in the mitochondrial membrane potential (p < 0.01) and the level of activated caspase 3/7 (p < 0.05) in prostate carcinoma cells. This study is the first to show that Dido induced cytotoxicity with high selectivity and higher potency than DHA in human prostate carcinoma cells. The mechanism of action is likely to involve an increase in the level of ROS, loss in the mitochondrial membrane potential as well as externalisation of phosphatidyl serine and increase in the caspase 3/7 activity. Dido may have potential to be used for the adjuvant therapy or combination therapy with conventional chemotherapeutic drugs. [Display omitted] •Didocosahexaenoin, an omega-3 derivative, induces cytotoxicity in prostate carcinoma cells.•The cytotoxicity induced by didocosahexaenoin in carcinoma cells was more potent than that afforded by DHA.•The likely mechanisms of cytotoxicity include an increase in the level of ROS and caspase 3/7 activity as well as an interruption in mitochondrial membrane potential.